Իմպլիկացիայի հասկացությունը տրամաբանության և լեզվաբանության մեջ - Լ. Գ. Բրուտյան (Հայկական ԽՍՀ գիտությունների ակադեմիա)
Понятие импликации, проникшее из логики в лингвистику, понимается неоднозначно не только в этих науках, но и внутри них. The concept of implication which has penetrated linguistics from logic is understood in different ways not only in these sciences but also inside them.
Keywords: B Philosophy; Psychology; Religion; Philology; Linguistics; Language and Literature; Logic; B Philosophy